The Effect of Online Learning Model (E-Learning) on the Prospective Teachers’ Concept Mastery - Verawati, Ni Nyoman Sri Putu; Sahidu, Hairunnisyah; Harjono, Ahmad; Hikmawati, Hikmawati; Gunada, I Wayan (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
During the Covid-19 pandemic, face-to-face learning has been replaced with online learning (e-learning). The learning process with this mode must be able to support the learning objectives towards understanding the concept. This study aims to explore the effect of e-learning on concept mastery in prospective teachers. In this study, we conducted a one group pretest posttest design, where one class group was used as the research sample and was given a pretest, treatment, and posttest. The sample was taken purposively with the criteria of prospective teacher students taking fundamental physics courses on motion kinematics material. The number of research samples was 23 prospective teachers at the Faculty of Teacher Training and Education, University of Mataram – Indonesia. The instrument in the form of an essay test is used to measure the understanding of the concept. Analysis of research data used descriptive statistical analysis (pair t-test) to test the research hypothesis. The results of the pair t-test showed a significance of p = 0.000 (< 0.05), this means that there is a significant difference between the pretest and posttest scores after the implementation of e-learning. The interpretation leads to the effect of online learning mode (e-learning) on the concept mastery ability of prospective teachers.